2015
DOI: 10.3390/ijms160922636
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 Fatty Acids and Cardiovascular Diseases: Effects, Mechanisms and Dietary Relevance

Abstract: ω-3 fatty acids (n-3 FA) have, since the 1970s, been associated with beneficial health effects. They are, however, prone to lipid peroxidation due to their many double bonds. Lipid peroxidation is a process that may lead to increased oxidative stress, a condition associated with adverse health effects. Recently, conflicting evidence regarding the health benefits of intake of n-3 from seafood or n-3 supplements has emerged. The aim of this review was thus to examine recent literature regarding health aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 138 publications
0
68
0
1
Order By: Relevance
“…Reperfusion is known to trigger a severe hemodynamic dysfunction via inflammatory and oxidative stresses (18). Although most clinical trials have shown Omega-3 supplementation in secondary prevention to be beneficial on the cardiovascular outcome, reducing coronary events and mortality, their clinical benefit remains controverted (11).…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusion is known to trigger a severe hemodynamic dysfunction via inflammatory and oxidative stresses (18). Although most clinical trials have shown Omega-3 supplementation in secondary prevention to be beneficial on the cardiovascular outcome, reducing coronary events and mortality, their clinical benefit remains controverted (11).…”
Section: Discussionmentioning
confidence: 99%
“…>20 C) n-3 polyunsaturated fatty acids (PUFAs), primarily eicosapentaenoic acid (EPA; 20:5 n-3) and docosahexaenoic acid (DHA; 22:6 n-3), are beneficial in the context of lowering cardiovascular disease morbidity and mortality (Walker et al, 2013;Maehre et al, 2015). Dietary VLC n-3 supplementation may also improve inflammatory conditions, such as rheumatoid arthritis (Calder, 2006;Spite, 2013), cognitive function (Flock et al, 2013;Huhn et al, 2015), and visual acuity of preterm children (Molloy et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…3,4 These alterations lead to the development and progression of chronic diseases, such as metabolic, neurological, pulmonary and cardiovascular diseases as well as cancer. 3,[5][6][7] In addition to the constituents with antioxidant activity, antimicrobial phytoconstituents are of interest because of problems of antibiotic resistance associated with the existing drugs. [8][9][10] In addition,…”
Section: Introductionmentioning
confidence: 99%